2019
DOI: 10.1016/j.scitotenv.2018.08.164
|View full text |Cite
|
Sign up to set email alerts
|

The Kobresia pygmaea ecosystem of the Tibetan highlands – Origin, functioning and degradation of the world's largest pastoral alpine ecosystem

Abstract: With 450,000 kmKobresia (syn. Carex) pygmaea dominated pastures in the eastern Tibetan highlands are the world's largest pastoral alpine ecosystem forming a durable turf cover at 3000-6000 m a.s.l. Kobresia's resilience and competitiveness is based on dwarf habit, predominantly below-ground allocation of photo assimilates, mixture of seed production and clonal growth, and high genetic diversity. Kobresia growth is co-limited by livestock-mediated nutrient withdrawal and, in the drier parts of the plateau, low … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(125 citation statements)
references
References 140 publications
2
122
0
1
Order By: Relevance
“…Author s changes in manuscript: The end of chapter 3.3 now reads: "Furthermore, the occurrence of synanthropic taxa has been observed in the nearby Damxung valley since 8.5 cal ka BP (Schlütz et al, 2007). This corroborates the strong anthropogenic influence on the formation and restructuring of vegetation patterns in the area but leaves a time gap of almost 3 ka between the evidence from Damxung valley and Nam Co.…”
Section: Interactive Commentmentioning
confidence: 73%
See 1 more Smart Citation
“…Author s changes in manuscript: The end of chapter 3.3 now reads: "Furthermore, the occurrence of synanthropic taxa has been observed in the nearby Damxung valley since 8.5 cal ka BP (Schlütz et al, 2007). This corroborates the strong anthropogenic influence on the formation and restructuring of vegetation patterns in the area but leaves a time gap of almost 3 ka between the evidence from Damxung valley and Nam Co.…”
Section: Interactive Commentmentioning
confidence: 73%
“…Furthermore, we adjusted the elevation limits in figure 4. Approximate biome elevations were taken from satellite imagery (Sentinel 2B) and herewith derived vegetation indices, field excursion and literature review (Wang and Yi, 2011;Ohtsuka et al, 2008).…”
Section: Comment 18mentioning
confidence: 99%
“…Detrending method: block averaging Time lags optimization: covariance maximization with default ±1 s Correction for air density fluctuations: application of WPL terms to fluxes (Webb et al, 1980) Spectral corrections: analytic high-pass filtering (Moncrieff et al, 2005) and analytic low-pass filtering (Moncrieff et al, 1997) this error is not evenly distributed but has a greater effect during daytime and summer when sensible heat fluxes are large. Fratini et al (2014) have shown that errors in mean concentrations leak into errors in fluxes on account of amplified or dampened estimated fluctuations.…”
Section: Drift Correctionmentioning
confidence: 99%
“…The majority of the TP is covered by the biggest pastural system in the world, the so-called steppe-meadow ecotone, consisting of 450 000 km 2 of Kobresia (syn. Carex) pygmaea pastures and 800 000 km 2 of alpine steppe ecosystem (Miehe et al, 2011;Miehe et al, 2019). With decreasing precipitation to the west, the K. pygmaea pastures are being replaced by alpine steppe ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, due to climate change and increased human disturbances, the high-altitude alpine grassland ecosystems, which are the dominant grassland vegetation type, have been severely degraded (Gao et al, 2010;Miehe et al, 2017;Qiao et al, 2015). The air temperature on the plateau has increased by 0.3 • C decade −1 , which is 3 times the global average .…”
mentioning
confidence: 99%